INCLUSIVE ISLAM IN AHMAD TOHARIâ€™S NOVELS - Mugijatna, Mugijatna (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2014)
Most of Ahmad Tohariâ€™s novels have something to do with Islam. Yet, study on the aspects of Islam in the novels is rare. As an NU santri, Ahmad Tohariâ€™s view on life is shaped by Islam according to NU's understanding. He wants to develop an understanding of Islam which is inclusive. There are two kinds of inclusivism. Inclusivism that considers that â€œtruthâ€ and â€œsalvationâ€ are available in other religions, that is, inclusivism in conviction and inclusivism that rejects this idea and limits inclusivism to social affairs only, the existence of other religions is simply respected. Ahmad Tohariâ€™s idea of inclusivism goes as far as to include inclusivism which accepts â€œtruthâ€ and â€œsalvationâ€ in other conviction. In the trilogy of Ronggeng Dukuh Paruk, Ahmad Tohari expresses his idea of a person who does not choose to embrace Islam as being embraced by Islam. In Lingkar tanah dan lingkar air, Ahmad Tohari expresses the idea of Islam which respects differences. In Kubah, Ahmad Tohari expresses an idea that Muslims should forgive sinners. The first belongs to inclusivism in conviction, while the second and the third belong to inclusivism in social affairs.